On the behavior of a self-exciting faraday disk homopolar dynamo with battery in the presence of an external magnetic field - Moroz, I (2001)
Goldbrum et al. [2000] investigated the biasing effects of including an external battery on the behavior of a self-exciting Faraday disk homopolar dynamo, originally introduced by Hide et al. [1996]. In this paper we return to the model of Hide [1997] and consider the additional effects of incorporating an external magnetic field on the dynamo.